Life after cancer and the communist order: A case study on grassroot patient organization in China - Ying Chen; Cheng Pang Lee (Elsevier, 2021)
Patient-led organizations have mushroomed in China over the past three decades, but they have not received enough academic attention. This paper aims to explore the survival logic of patient-led organizations and forge a critical analysis of the imbrications of patient life and state power in a non-neoliberal context of contemporary China. Based on seven months of ethnographic fieldwork and 41 interviews, we examine the case of the Shanghai Cancer Recovery Club (SCRC) as an example of a highly mobilized cancer survivorship that evolved from a group practicing Qigong. Unlike its counterparts in the liberal societies, SCRC has a completely different historical process of group formation. Decades ago, Chinese cancer patients believed that pre-modern "Qi" could control cancer, so they gathered to practice Qigong. To unify and better promote Qigong among cancer patients, they later formed a more organized Qigong milieu. After the Qigong fever, Qigong groups formed by cancer patients gradually evolved and registered as an official cancer social organization. Based on the idea of Chinese values of collective living and the revolutionary spirit of communism, SCRC promoted very innovative "group cancer-fighting method" (e.g., grassroots based, large-membership, and motivating slogans). Through these, they have succeeded in building a citywide network that reaches down to the street level. As the oldest and largest patient-led organization in contemporary China, SCRC serves as the Shanghai model that has influenced hundreds of similar patient-led organizations in other cities. We further argue that SCRC has played three roles in the current medical system: as a welfare arm of the government, as a collaborator with medical institutions, and as a mediator between the public and patients.